Optimization of Alkali Catalyzed Transesterification of Safflower Oil for Production of Biodiesel - M. C. Math; K. N. Chandrashekhara (Journal of Engineering)
The Central Composite Design is used for the optimization of alkaline catalyzed transesterification parameters such as methanol quantity, catalytic concentration, and rotational speed by keeping the temperature and reaction time constant. The Central Composite Design method is employed to get the maximum safflower oil methyl ester yield. The combined effects of catalyst concentration, rotational speed, and molar ratio of alcohol to oil were investigated and optimized using response surface methodology. A statistical model has predicted the maximum yield of safflower oil methyl ester (94.69% volume of oil) parameters such as catalyst concentration (0.6 grams), methanol amount (30 mL), rotational speed (600 rpm), and keeping constant reaction temperature (55°C to 65°C) and reaction time (60 minutes). Experimental maximum yield of 91.66% was obtained at above parameters. XLSTAT is used to generate a linear model to predict the methyl ester yield as a function of methanol quantity, catalyst concentration, and rotational speed by keeping constant reaction temperature (55°C to 65°C) and reaction time (60 minutes). MINITAB is used to draw the 3D response surface plot and 2D contour plot to predict the maximum biodiesel yield.